PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA ANTARA KELOMPOK SISWA YANG MENDAPATKAN PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DENGAN STUDENT TEAMS ACHIEVEMENTS DIVISIONS (STAD) (Institut Pendidikan Indonesia, 2014)
Abstract :This research use two tipe cooperatif learning, they are Teams Games Tournament and Student Teams Achievement Division. The study in this approach guided student’s attention to learn to understand the problem, how to, and what needed to solve matematik problem. The purpose in this research is to know the difference of increase problem solving of mathematics student ability who use Teams Games Tournament and Student Teams Achievement Divisions, with the significant is 5 %. Increase problem solving student of mathematic ability student who gets cooperatife learning type Teams Games Tournament different with students who gets Student Teams Achievement Division learning. Abstrak :Penelitian ini menggunakan 2 jenis pembelajaran kooperatif, yaitu Teams Games Tournament dan Student Teams Achievement Division. Pembelajaran kooperatif ini mengarahkan perhatian siswa untuk mempelajari, memahami masalah, bagaimana, dan apa yang dibutuhkan untuk menyelesaikan suatu masalah matematika. Tujuan penelitian ini adalah untuk mengetahui perbedaan peningakatan kemampuan pemecahan masalah matematik siswa yang menggunakan metode Teams Games Tournament dan Student Teams Achievement Division. Dengan taraf signifikan 5 %. peningkatan kemampuan pemecahan masalah matematik antara siswa yang mendapatkan pembelajaran kooperatif tipe Teams Games Tournament berbeda dengan siswa yang mendapatkan pembelajaran Student Teams Achievement Division.